Zeolite/Hydrilla verticillata Composite for the Adsorption of Naphthol Blue Black Dye - Roza Ruspita; Muhamad Fajar Muarif; Ade Irmadiki Agipa; Ayu Sabila Yulizar; Mareta Silpiana; Fara Amalia (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
In this study, a zeolite/Hydrilla verticillata composite adsorbent was prepared and characterized, and its performance was evaluated for the adsorption of Naphtol Blue Black (NBB) dye. Natural zeolite sourced from Bayah, Banten, was used as the base material. The composite was synthesized using the wet impregnation technique. Characterization was conducted using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM). FTIR analysis showed absorption bands at 2919 cm-1, 514 cm- 1, and 1014 cm-1, indicating the successful formation of the zeolite/Hydrilla verticillata composite. XRD results revealed that the Bayah natural zeolite contains modernite and heulandite crystal phases, with an average crystallite size of 9.3 nm calculated using the Scherrer equation. SEM images indicated that the zeolite surface was largely covered by Hydrilla verticillata particles. The adsorption experiment showed that the composite adsorbent achieved a 34.07% removal efficiency of NBB dye. The adsorption process followed the Freundlich isotherm model, with an R2 value of 0.9995 and a maximum adsorption capacity of 13.59 mg/g.